Tolerability of high doses of lercanidipine versus high doses of other dihydropyridines in daily clinical practice: the TOLERANCE Study - V. Barrios; C. Escobar; M. de la Figuera; J. L. Llisterri; J. Honorato; J. Segura; A. Calderón (Кардиоваскулярная терапия и профилактика)
Aim. The TOLERANCE study was aimed to compare the tolerability of high doses of lercanidipine (20 mg) with that of other frequently used dihydropyridines (amlodipine 10 mg/nifedipine GITS 60 mg) in the treatment of essential hypertension (EAH) in daily clinical practice. Material and methods. It was an observational, transversal, multicentre study performed in a Primary Care Setting. A total of 650 patients with EAH and age ≥18 years were included. They had been treated with high doses of lercanidipine (n=446) or amlodipine/nifedipine GITS (n=204) during at least 1 month and previously with low doses (10 mg, 5 mg, and 30 mg, respectively) of the same drugs. Results. The main objective was to compare the rates of vasodilation-related adverse events (AE) between both groups. Rates of signs and symptoms related to vasodilation were significantly higher (p<0,001) in the amlodipine/nifedipine GITS group (76,8%, CI 95% [70,7;82,9]) than in lercanidipine group (60,8%, [56,1;65,5]). Blood pressure control (<140/90 mm Hg or <130/80 for diabetics) and type of concomitant antihypertensive medications were similar in both groups. Treatment compliance was good (~93%) and fairly comparable in both groups. Most AE with lercanidipine were mild (74,5% vs. 64% in amlodipine/nifedipine GITS group, p=0,035) whereas severe AE rates did not differ significantly between groups (2,8% vs. 3,6%). Conclusion. In conclusion, treatment with lercanidipine at high doses is associated with a lower rate of AE related to vasodilation compared to high doses of amlodipine or nifedipine GITS in clinical practice.